2015
DOI: 10.1016/j.palaeo.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of climate and aeolian dust input in calcrete formation in volcanic islands (Lanzarote and Fuerteventura, Spain)

Abstract: Calcretes are widely described in non-marine settings with carbonates in their catchment, or vicinity areas, but in volcanic islands without carbonates in their substrate, calcretes are not very common. In Lanzarote and Fuerteventura Canary Islands, characterized by impressive volcanic landscapes, the sedimentary carbonate rocks are rare except for some recent marine and aeolian deposits. In these settings very well-developed calcretes cover large areas of the present landscape. The source of calcium required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 63 publications
1
18
1
Order By: Relevance
“…The present study demonstrated that the Ca contribution from in situ weathering is significant, which is different from many other studies emphasizing a dominance of atmospheric inputs (i.e. Quade et al, 1995;Capo and Chadwick, 1999;Chiquet et al, 1999;Hamidi et al, 2001;Van der Hoven and Quade, 2002;Rech et al, 2003;Lintern et al, 2006;Dart et al, 2007;Huerta et al, 2015). Only three studies reported a dominance of in situ weathering i.e.…”
Section: What Mechanisms Influence the Respective Contributions Of Thcontrasting
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated that the Ca contribution from in situ weathering is significant, which is different from many other studies emphasizing a dominance of atmospheric inputs (i.e. Quade et al, 1995;Capo and Chadwick, 1999;Chiquet et al, 1999;Hamidi et al, 2001;Van der Hoven and Quade, 2002;Rech et al, 2003;Lintern et al, 2006;Dart et al, 2007;Huerta et al, 2015). Only three studies reported a dominance of in situ weathering i.e.…”
Section: What Mechanisms Influence the Respective Contributions Of Thcontrasting
confidence: 99%
“…For instance, in Morocco, Hamidi et al (2001) stated that dust is the main Ca source of secondary carbonates observed on a Ca-rich bedrock, 200 km inland. In the Canaries Island, Huerta et al (2015) studied secondary carbonates on Ca-rich bedrocks close to the coastline and they considered dust as the main Ca source instead of sea spray. In the Far North Region of Cameroon, 1000 km inland, the present study emphasized the importance of the in situ weathering, especially on Carich bedrock.…”
Section: What Mechanisms Influence the Respective Contributions Of Thmentioning
confidence: 99%
“…1a). African dust is reported as a component of modern soils on the Canary Islands (Muhs et al, 2010) and is also found in paleosols of Pleistocene age (Huerta et al, 2015;Muhs et al, 2016;Menéndez et al, 2019;Roettig et al, 2019). These studies have demonstrated the presence of an African dust component by identification of minerals exotic to the Canary Islands.…”
Section: Introductionmentioning
confidence: 93%
“…However, the sample with the lowest δ 13 C was the one containing trace amounts of quartz (sample CAL‐5), not present in Gran Canaria rocks, but of aeolian origin. Consequently, quartz may be accompanied by variable amounts of carbonate grains derived from marine limestones (Menéndez et al ., ; Huerta et al ., ). If this sample is excluded, the δ 13 C range changes to +5·84 to +4·84‰ VPDB (mean = +5·47‰), whereas the range in δ 18 O remains invariable.…”
Section: Description Of the Calabozo Carbonate Depositmentioning
confidence: 97%